OCIMUM BASILICUM L. ESSENTIAL OIL COATED BIOMATERIAL SURFACES PREVENT BACTERIAL ADHESION AND BIOFILM GROWTH - Rajaraman, Sivarama Krishnan; Jainu, Mallika; Dhakshinamoorthy, Gnanaprakash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Biomaterials associated infection is the most common issue associated with the biomaterial implants regardless of its form or function. Bacteria form colonies and this result in the formation of biofilm on the surface, making the infection unreceptive to antibiotics and host defense mechanisms. The implant is removed as an outcome. Medicinal plants have widespread usage for their active biomolecules, and the study of their antimicrobial activities has gained widespread importance. Methods: In this study, the essential oil of Ocimum basilicum L. (OB) is coated on biomaterial surfaces to study their efficacy in preventing bacterial colonization and biofilm formation. The essential oil is coated on polymethylmethacrylate and polystyrene substratum surfaces. Gram-positive bacteria, including Staphylococcus aureus and Staphylococcus epidermidis, and Gram-negative bacteria, including Escherichia coli and Pseudomonas aeruginosa, are allowed to adhere and grow for 1 hr, 3 hrs, and 24 hrs. Results: The number of bacteria adhering to the coated surfaces is significantly less (**p<0.01) compared to uncoated surfaces, at the measured instances of time. The zone of inhibition of the essential oil is observed for both Gram-positive and Gram-negative bacteria. Maximum inhibition was observed for S. aureus (30±1.2 mm diameter) compared to S. epidermidis (28±0.8 mm diameter), E. coli (25±1.1 mm diameter), and P. aeruginosa (21±0.6 mm diameter). Conclusion: The study reveals potent bacteriostatic effects of OB essential oil on both Gram-positive and Gram-negative bacteria. Thus, OB. essential oil serves to be a promising coating on the implant surfaces for preventing bacterial adhesion and biofilm growth. Keywords: Biomaterials, Bacterial adhesion, Biofilm, Ocimum bacilicum L., Antibacterial coating.